TEMPERATURE REGIME OF MELT IN ROLL CRYSTALLIZER AT CONTINUOUS CASTING OF REINFORCED TAPE - E. F. Baranovski; V. M. Iljushenko; T. M. Rubanova (Литьë и металлургия, 2005)
The analytical study of heat exchange in roll crystallizer at casting of armored belt of chlorine copper is carried out. The influence of the casting speed at the temperature regime of tub is studied. The temperatures of the melt cast molding are determined.